Ether‐Soluble Cu53 Nanoclusters as an Effective Precursor of High‐Quality CuI Films for Optoelectronic Applications. Issue 3 (11th December 2018) - Yuan, Peng; Chen, Ruihao; Zhang, Xiaomin; Chen, Fengjiao; Yan, Juanzhu; Sun, Cunfa; Ou, Daohui; Peng, Jian; Lin, Shuichao; Tang, Zichao; Teo, Boon K.; Zheng, Lan‐Sun; et al.
Abstract: An effective strategy is developed to synthesize high‐nuclearity Cu clusters, [Cu53 (RCOO)10 (C≡CtBu)20 Cl2 H18 ] + (Cu53 ), which is the largest Cu I /Cu 0 cluster reported to date. Cu powder and Ph2 SiH2 are employed as the reducing agents in the synthesis. As revealed by single‐crystal diffraction, Cu53 is arranged as a four‐concentric‐shell Cu3 @Cu10 Cl2 @Cu20 @Cu20 structure, possessing an atomic arrangement of concentric M12 icosahedral and M20 dodecahedral shells which popularly occurs in Au/Ag nanoclusters. Surprisingly, Cu53 can be dissolved in diethyl ether and spin coated to form uniform nanoclusters film on organolead halide perovskite. The cluster film can subsequently be converted into high‐quality CuI film via in situ iodination at room temperature. The as‐fabricated CuI film is an excellent hole‐transport layer for fabricating highly stable CuI‐based perovskite solar cells (PSCs) with 14.3 % of efficiency. Abstract : An effective strategy is developed to synthesize high‐nuclearity Cu53 clusters that are surface‐capped by alkynyl and acetate ligands. These nanoclusters are unexpectedly soluble in ether, enabling the easy formation of high‐quality films. The cluster films are readily converted into high‐quality CuI thin films for applications as a hole transport layer in perovskite solar cells.